Evaluation of the Maggot Cultivation Labour Intensive Program Using the CIPP Model - Aisya Septia Cahyaning Puteri; Susi Hardjati (Publik : (Jurnal Ilmu Administrasi), 2026)
Poverty remains a major socioeconomic challenge in Indonesia, requiring effective and sustainable intervention programs. One initiative implemented by the Surabaya City Government is the Maggot Cultivation Labour Intensive Program, designed to generate employment opportunities while supporting community-based economic empowerment. This study evaluates the implementation of the program in Krembangan District using the Context, Input, Process, Product (CIPP) evaluation model. A descriptive qualitative approach was employed through interviews, observations, and document analysis involving program stakeholders and beneficiaries. The findings indicate that, from the context perspective, the program addresses local needs in areas characterized by relatively high unemployment and poverty. However, the input evaluation reveals limited community participation, inadequate facilities and infrastructure, and insufficient availability of raw materials. Process evaluation identifies weaknesses in stakeholder coordination, inconsistent monitoring, and technical implementation that has not yet achieved expected production targets. Product evaluation demonstrates that the program has not significantly improved participants' income or economic independence, while diversification of business outcomes remains limited. Overall, although the program shows relevance as a poverty reduction strategy, its effectiveness is constrained by institutional, technical, and participatory challenges. Strengthening stakeholder collaboration, improving resource provision, enhancing capacity-building activities, and establishing more consistent monitoring mechanisms are recommended to increase program sustainability and maximize its contribution to local poverty alleviation.